Penerapan Prinsip Demokrasi dalam Sistem Pemilihan Umum di Indonesia Perspektif Fiqh Siyasah - Bustomi, Imam (Cv. Kalimasada Group, 2023)
Since the reform era began in 1998 in Indonesia, political transformation has been significant. This period not only marked the end of the authoritarian government under President Soeharto, but also paved the way for changes in the political and constitutional system in Indonesia. This change not only changes the way of life of the people, but also changes the constitutional system of the Indonesian nation through amendments to the 1945 Constitution of the Republic of Indonesia. Article 1 paragraph (2) of the 1945 Constitution reads,